Random disturbance in cavity boundaries. Issue 1 (January 2021) - Wang, Kangjian; Rong, Guang; Mu, Qing; Yin, Hongqiao
Abstract: The water condition usually is complicated due to many uncertain factors such as internal wave, density differences and so on. So the real cavity boundaries is hard to predict for a supercavition projectile. In this work, a random disturbance model is established based on Poison process of random mathematics. This model is employed to the Logvinovich cavitation expansion equation for simulating a cavity in real ocean environment. A detail of cavity outline is obtained by this calculation. The results indicate that the cavitation boundary of higher velocity case is smoother than lowers. The parameter λ of Poison model is a key factor of disturbance frequency, which largely affects the length of cavity. The λ is proportion to the cavity length. This provides a new method for water environment cavity analysis.